Errors and misconceptions in solving linear inequalities in one variable - Samuel Kojo Biney; Clement Ayarebilla Ali; Nixon Saba Adzifome (Journal of Advanced Sciences and Mathematics Education, 2023)
Linear inequalities are mathematical expressions that compare two expressions using the inequality symbol, in either be algebraic or numerical or both. However, in solving either of these types some student-teachers commit errors that have been backed by associated misconceptions. This research examined these errors and the associated misconceptions thereafter. Guided by two research questions, the researchers adopted the qualitative narrative inquiry design. The purposive sampling was employed to select 15 student-teachers who met the best requirement that fits the purpose, problem, and objective of a qualitative narrative inquiry. The main instruments were interview guides, where the participants and researchers collaborated with each other to ensure that the story was properly told and aligned with linear inequalities through field notes, observations, photos and artefacts. The narrative analysis started with verbatim transcription of the narratives and ended with deductive coding. The results were scanned copies of participants’ sample narratives that were pasted at appropriate places and discussed. Consequently, it was concluded that student-teachers lacked the basic rules, procedural fluency and skills, and formulation of linear inequalities. These errors emanated from misconceived methods and rote memorization. It was therefore recommended that educators imbibe practical and everyday methodologies into the teaching and learning of linear inequalities.